Physical Health and Cognitive Function Independently Contributed to Functional Disability among Chinese Older Adults: Data from Two Asian Metropolises - Lei Feng; Tze-Pin Ng; Yanling He; Chunbo Li; Ee-Heok Kua; Mingyuan Zhang (Journal of Aging Research)
Objective. We aimed to examine the independent contributions of physical health and cognitive function to disability among Chinese older adults living in two Asian metropolises and explore the potential influences of environment. Design and Participants. Cross-sectional analysis based on data from two population-based studies: the Shanghai Survey of Alzheimer's Disease and Dementia (n=4639) and the Singapore Longitudinal Ageing Study (n=2397). Disability was defined as needing help in at least one activity of daily living. Results. The prevalence of functional disability was higher in Shanghai sample (5%) than that in Singapore sample (1.8%). Number of chronic diseases, self-rated health status, cognitive function (measured by the Mini-Mental State Examination), and environment (Singapore versus Shanghai) significantly contributed to functional disability independent of each other. The adjusted Odds Ratio was 1.35 (95%CI 1.22–1.50), 2.85 (95% CI 2.36–3.43), 0.89 (95% CI 0.85–0.94), and 0.68 (95% CI 0.48–0.96), respectively. The strength of associations between health variables and disability appeared to be influenced by environment. Conclusion. Physical health and cognitive function independently contributed to functional disability. The associations are modulated by environmental factors.